2023
DOI: 10.3389/fphys.2023.1195604
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in long-term effects of collagen-induced arthritis in middle-aged mice

Bernhard Maximilian Schuh,
Kristína Macáková,
Andrej Feješ
et al.

Abstract: Introduction: Rheumatoid arthritis (RA) is a chronic inflammatory disorder with high prevalence among middle-aged women. Collagen-induced arthritis (CIA) is the most widely used animal model of RA, however, sex differences and long-term effects of CIA in mice are poorly described in the literature.Aim: Therefore, the present study aimed to analyze the long-term effects of CIA on the joints of middle-aged mice of both sexes and to describe potential sex differences.Materials and methods: CIA was induced in midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The first limitation is that we used only male mice as arthritis models. Schuh et al [ 51 ] showed that male mice developed arthritis earlier than female mice and suffered more severe bone and joint destruction while still displaying similar arthritis severity as females. Therefore, it is possible that female CIA mice might display different expression pattern of IL-6 in OB.…”
Section: Discussionmentioning
confidence: 99%
“…The first limitation is that we used only male mice as arthritis models. Schuh et al [ 51 ] showed that male mice developed arthritis earlier than female mice and suffered more severe bone and joint destruction while still displaying similar arthritis severity as females. Therefore, it is possible that female CIA mice might display different expression pattern of IL-6 in OB.…”
Section: Discussionmentioning
confidence: 99%